Results of self-assessment of health status of school-age children living in rural areas - K. E. Moiseeva; Yu. V. Kondratieva; A. V. Alekseeva; Sh. D. Kharbedia (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The objective was to assess the health status of school-age children living in rural areas.Material and methods. The study was carried out by the method of the main array by anonymous questioning of 106 schoolchildren of grades 7–11 at the age of 12–17 years, trained in the municipal general education institution «Secondary School № 1» in the city Dno of the Pskov Region. The information obtained from Form № 026/y-2000 was used for an objective assessment.Results. We determined that 52.8 % of the children who studied at the rural school in grades 7–11 were girls whose average age was (14.72±0.2) years, brought up in a full family (69.8 %) with two children (48.2 %), with a good financial situation (52.9 %). Studying self-esteem of schoolchildren’s health showed that the average score set by children was (3.86±0.08). Girls are worse than boys, they evaluate their health. The study of the frequency of acute diseases in children and the number of days missed by them due to disease during the school year showed that the average number of diseases was (1.61±0.19) times, the number of missed days was (7.9±0.76) days. We found out that only 18.8 % of children did not go to school when they were sick. 63.2 % of children were engaged in sports, while 30.2 % were engaged in sports regularly. All 100.0 % of boys were more or less engaged in sports, among them 64.0 % of schoolchildren were regularly engaged in sports. Among girls, no one was regularly engaged in sports, 30.4 % was irregularly engaged in sports. Studying the attitude of schoolchildren to smoking and drinking alcoholic drinks showed that 8.5 % of schoolchildren smoked regularly, 15.1 % of schoolchildren drank low-alcohol drinks from time to time, 18.9 % – wine, and 4.7 % of schoolchildren – strong spirits. According to medical records, more than half of schoolchildren had disharmonious physical development (55.8 %). The estimation of the distribution of children by health groups showd that among schoolchildren the proportion of children of group I was 21.4 %, group II – 59.1 %, group III – 17.7 %, group IV – 1.8 %, groups V – 0 %.Conclusion. Indicators of self-assessment of schoolchildren’s health and the proportion of children involved in sports in the Pskov Region were lower than on the average in the Russian Federation. The health level of schoolchildren living in rural areas was lower than the average Russian indicators.